Estimation of energy saving by nanofluid operated air conditioning system / Mohd Hafiz Abdul Halim Shah - Mohd Hafiz , Abdul Halim Shah (2013)
Nanotechnology enhancement, thermal engineering and thermal science lead to interest in development of new technology of fluids known as nanofluid. Nanometer particle size is added into base fluids are known as nanofluids material. Nanofluids is a new engineering material which use in many heat transfer application. Nanofluids offer high surface to volume ratio and compactness material compare to conventional fluids. Nanofluid has drawn high attention from researcher since it has superior thermal properties. These superior thermal properties can be used in many industries such as electronic, chemical engineering, microelectronic, transportation, manufacturing and aerospace. In such electronic industries, nanofluids offer better cooling compare to conventional fluids. Entire analysis is conducted with air condition system which operated with nanofluids as medium for heat transfer. The analysis is conducted under the influences of volume fraction on nanofluids such as Cu-H2O, Al2O3-H2O, Cu-Eg and Al2O3-Eg. Further analysis is conducted under influences of heat exchange parameter with nanofluids present as medium of heat transfer. Analysis is performance for internal side of heat exchanger only. Thermal physical properties are important parameter for energy saving in nanofluids air condition operated system. Thermal conductivity, density, viscosity and specific heat are main thermal physical properties which play roles in determination of energy uses in air conditioning system. Enhancement of thermal conductivity gives nanofluids, a suitable selection to be used as medium of heat transfer in air conditioning to save energy used during operation. Method to determine energy saving is calculating increment of energy ratio for air conditioning system with nanofluids and compare to air condition system which operates with base fluids. On top of that, energy saving for nanofluids can be measured by determines pumping power required by air condition with nanofluids application to base fluids application. Energy saving of air condition operated with nanofluids can be achieved. Selections of nanofluids are important since not entire nanofluids give signification or increment result after implementation. Alumina oxide with water give the highest increment of energy saving and copper with ethylene glycol do not result any positive result. Thermal conductivity is of the important parameter in determination of energy saving for air condition. Particle shape, particle polydisperity and particle agglomeration could be a function in determination of thermal physical of nanofluid. Further study and research is a must to clarify these variables. Anyhow, nanofluids preparation is a major challenge at present and this may limit nanofluids further research and application.